Negotiating Text and Context: The Hadith on the Prohibition of Women’s Travel Without a Maḥram in the Social and Legal Histories of Saudi Arabia and Indonesia - Armila, Nizma; Falah, Mega Satria Nurul (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study investigates the differing interpretations and applications of the hadith prohibiting women from traveling without a maḥram in Saudi Arabia and Indonesia. Through a comparative analysis grounded in historical, legal, and socio-cultural contexts, the research reveals that Saudi Arabia traditionally applies the hadith in a strict, textualist manner, rooted in the Ḥanbalī legal tradition and guardianship system. Indonesia, influenced by pluralistic scholarship and social realities, adopts a more flexible, contextualist approach through ijtihād by religious organizations. Despite these differences, the study affirms that the original ruling remains valid: a woman traveling without a maḥram is impermissible (ḥarām) unless in rare, necessity-based exceptions. The presence of a maḥram is not merely ideal but a critical safeguard upheld throughout Islamic legal history to protect women’s dignity (ʿirḍ) and safety (nafs). In modern contexts where security may seem assured, Muslim women must still prioritize obedience to Allah and His Messenger, over social convenience or personal autonomy. Modern adaptations must not override divine directives. Thus, the hadith's relevance continues, and contextual flexibility must remain within the bounds of Sharīʿah—aimed at upholding the protective purpose of Islamic law rather than promoting unrestricted freedom.